HABILIDADES SOCIAIS E CONSUMO DE SUBSTÂNCIAS PSICOATIVAS – ESTUDO COM PACIENTES EM TRATAMENTO AMBULATORIAL - BARBOSA, VIVIAN MIUCHA MOURA (2018)
The present theme is in the field of mental health and quality of life, considering social skills as a set of behaviors of a person in an interpersonal situation, through which this person manifests their desires, attitudes, feelings, opinions or rights so appropriate. Socially skillful behavior refers to the expression of attitudes, feelings, opinions, desires, respecting oneself and others, and there is usually a resolution of the immediate problems of the situation and a decrease in the likelihood of future problems. It is important that individuals learn to manage their psychological charac-teristics that expose them to a situation of risk, enhancing those that can protect them against the consumption of psychoactive substances. Damage to social skills can contribute to drug use, as users use the drug as a maladaptive way to deal with external pressures and interpersonal situations. Being socially awkward leads to worse responses to drug use, making it difficult to refuse drugs especially in close relationships. The present study aimed to evaluate the social skills of patients on outpatient treatment and the correlation with the use of psychoactive substances. This is a cross-sectional, cross-sectional descriptive study (N = 60). The instruments used were: Sociodemographic Questionnaire, Social Skills Inventory (IHS), Ques-tionnaire on adult drug use Assist (Alcohol, Smoking and Substance Involvement Screening Test). The results indicated that the patients presented a good average of social skills repertoire, which may be related to the fact that they are already in treatment and have some autonomy in the management of their routine. The data indicated a correlation between marijuana use and the Factor Facing and High Af-firmation with Risk, which indicates greater inability to deal with feelings and reac-tions generated in social situations and can contribute to the search of the substan-ce as non-assertive behavior of coping with these situations .